Spectrum of causative mutations in patients with haemophilia A in Austria - Reitter, Sylvia; Sturn, Rümuth; Horvath, Birgit; Freitag, Renate; Male, Christoph; Muntean, Wolfgang; Streif, Werner; Pabinger, Ingrid; Mannhalter, Christine; and the Austrian Molecular Haemophilia Study Group (Thrombosis and Haemostasis, 2010)
In patients with haemophilia A knowledge of the pathogenetic mutation is important i) as basis for carrier diagnosis and ii) for risk estimation of inhibitor formation. The pathogenetic mutations were identified by testing inversions in intron 1 and 22 (IVS22 and IVS1) and sequencing part of the promoter, the coding region and the exon/intron boundaries in a cohort of Austrian haemophilia A patients. A total of 239 patients from nine participating centres, who had consented to genetic testing and of whom clinical information was available were included in the study. First, IVS22 and IVS1 were tested; in case of absence of either inversion patients were subjected to sequencing. Mutations within the FVIII gene were identified in 234 patients. Notably, 53 mutations had not previously been described in HAMSTeRS. Of our patient cohort, 72.5 % had either an IVS22 or a missense mutation. Interestingly, in three brothers with severe haemophilia, we found a double mutation in exon 14 (missense + small deletion). The spectrum of mutations in Austrian haemophilia A patients was comparable to that found in the German and Italian population; however, it differed from the spectrum reported in the UK. In conclusion, 53 not previously published mutations were identified in Austrian haemophilia A patients. The occurrence of double mutations in the factor VIII gene could be confirmed and their low frequency was corroborated. We speculate that the differences between mutations in Austria and other European countries are due to ethnic diversity. Detailed investigations of the association of ethnicity and the mutation spectrum are planned.
Keywords: Austria; haemophilia; mutation analysis